NEW TYPE OF GYPSUM BASED LIQUID MIXTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The dry construction plasters production (DCPP) is much younger than in other sectors of the construction industry. However, in this short period of time, dry construction plasters (DCPP) are taking their rightful place in finishing and waterproofing works construction. The DCPP use in the finishing work increases labor productivity by 2-3 times and significantly improves quality. This article presents the research results on dry construction plaster mixtures that improve the thermal insulation properties while maintaining the construction technical properties on the basis of local raw materials. Nowadays, the demand for construction materials modern quality types is growing significantly.